Reactive nitrogen in and around the northeastern and mid-Atlantic US: sources, sinks, and connections with ozone - M. Huang; M. Huang; G. R. Carmichael; K. W. Bowman; I. De Smedt; A. Colliander; M. H. Cosh; S. V. Kumar; A. B. Guenther; S. J. Janz; R. M. Stauffer; A. M. Thompson; et al. (Atmospheric Chemistry and Physics)
This study describes the application of a regional Earth system model with updated parameterizations for selected land–atmosphere exchange processes and multiplatform, multidisciplinary observations. We estimate reactive nitrogen (Nr = NOy+ NHx) emissions from various sources, surface and column nitrogen dioxide (NO2), and total and speciated Nr dry and wet deposition during 2018–2023 over the northeastern and mid-Atlantic US where nitrogen-oxide-limited or transitional chemical regimes dominate. The estimated Nr concentrations and deposition fluxes are related to ozone (O3) in terms of spatiotemporal variability and its key drivers as well as possible ecosystem impacts. Modeled surface O3 persistently agrees well with observations, with root mean square errors staying within 4–7 ppbv for individual years in May–June–July. Model-based surface O3–NO2 column correlation, which shows a dependency on column formaldehyde /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="880d1b22cfae9b4167ff115d05c6894c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1449-2025-ie00001.svg" width="8pt" height="14pt" src="acp-25-1449-2025-ie00001.png"/></svg:svg> NO2, is higher in 2020 (r=0.62) than in other years (r=0.47–0.56). Ozone vegetative uptake overall dropped by ∼10 % from 2018 to 2023, displaying clearer downward temporal changes than total Nr deposition as declining NOy emission and deposition competed with increasing NHx fluxes. It is highlighted that temporal variabilities of Nr and O3 concentrations and fluxes on subregional to local scales respond to hydrological variability that can be influenced by precipitation and controllable human activities like irrigation. Deposition and biogenic emissions that are highly sensitive to interconnected environmental and plant physiological conditions, plus extra-regional sources (e.g., O3-rich stratospheric air and dense wildfire plumes from upwind regions), have been playing increasingly important roles in controlling pollutant budgets as local emissions decline owing to effective emission regulations and COVID lockdowns.